Religião e empreendedorismo no Brasil : uma análise utilizando modelos de escolha ocupacional a partir do Censo de 2010 - Vieira, João Pedro Valentini Speggiorin (2015)
The objective of this study is to evaluate the influences of different religions on entrepreneurship in Brazil using models of occupational choice and microdata from the 2010 demographic census. Over the past 100 years entrepreneurship has been a central theme of research to leading economists. Although the literature in the macroeconomic scope presents a consensus on its contribution to the growth and economic development of a country it is in the microeconomic scope that lies the biggest challenge to understand what are the factors that lead the individuals to make a choice between whether or not to be an entrepreneur. The decision of an individual takes into account various factors, some of which are their personal values and principles. In this context religions have historically played a central role in society, serving as a provider of doctrines and values to their followers. The empirical strategy adopted employed discrete choice models in the estimation of occupational choice, using microdata from the 2010 census. The results showed that there are diverse effects of different religions on the choice of the individual to be or not an entrepreneur. There where also differences observed for the religious groups when we divide the entreprenuership variable in to two variables, employer and self emplyed.